Dynamics of Sky Brightness during a Hybrid Solar Eclipse using SQM - Jufriansah, Adi; Pramudya, Yudhiakto; Khusnani, Azmi; Hikmatiar, Hamzarudin; Sahlan, Sahlan; Saharul, Saharul; Donuata, Pujianti Bejahida (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
This study aims to analyze sky brightness dynamics during a hybrid solar eclipse using the Sky Quality Meter (SQM). Strategic observation sites were selected along the eclipse path, and continuous data collection was conducted using the SQM-LU-DL, telescopes, weather stations, and GPS for accurate location and atmospheric data. Measurements began several days before the eclipse and continued throughout and after the event. Data collected included sky brightness, visual documentation, and atmospheric conditions, which were analyzed using GnuPlot to detect trends and patterns in brightness changes. The study revealed significant fluctuations in temperature and light frequency, with a sharp decrease at the eclipse's peak, followed by a return to normal levels. These findings emphasize the eclipse's impact on natural light intensity and highlight the importance of addressing light pollution. The study contributes to understanding astronomical phenomena's effects on the environment and human health, aiding in the development of effective light pollution mitigation strategies.